2010
DOI: 10.1165/rcmb.2008-0472oc
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Decreases Alveolar Epithelial Fluid Transport via a Direct Inhibition of the Epithelial Sodium Channel

Abstract: Hypoxia and epithelial stretch that are commonly observed in patients with acute lung injury have been shown to promote the release of serotonin (5-hydroxytryptamine, 5-HT) in vitro. However, whether 5-HT contributes to the decrease of alveolar epithelial fluid transport, which is a hallmark of lung injury, is unknown. Thus, we investigated the effect of 5-HT on ion and fluid transport across the alveolar epithelium. 5-HT caused a dose-dependent inhibition of the amiloride-sensitive current across primary rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…It was shown that serotonin decreases alveolar epithelial fluid transport via a direct inhibition of epithelial sodium channel [8] . Many studies suggest that defects in alveolar epithelial fluid transport can lead to pulmonary edema [5] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that serotonin decreases alveolar epithelial fluid transport via a direct inhibition of epithelial sodium channel [8] . Many studies suggest that defects in alveolar epithelial fluid transport can lead to pulmonary edema [5] .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found that ENaC is the major determinant of alveolar fluid clearance across the alveolar epithelium. Earlier studies have demonstrated that serotonin (5-HT) significantly inhibits amiloride-sensitive sodium transport across rat and human lung alveolar epithelial cell monolayers via a receptor-independent inhibition of ENaC activity [8] . As 5-HT also significantly inhibits the amiloride-sensitive fraction of the alveolar fluid clearance in mice, 5-HT can be considered as an endogenous inhibitor of ENaC.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ENaC subunit expression and elevated ENaC activity can significantly promote AFC. [20] mTORC2 is a PIKK family member, which is composed of mTOR, Rictor, mSIN1, PRR5, and mLST8. This compound is rapamycin insensitive and plays an important role in the regulation of sodium transport channels and the protein translation process.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT also has a variety of important endocrine-like functions outside of the CNS, which include its ability to regulate vasoconstriction, proliferation, osteoclastogenesis, insulin secretion, and platelet function (1)(2)(3)(4)(5)(6)(7). The literature also suggests that 5-HT is an important regulator of the immune system with a role in the pathogenesis of autoimmunity (8,9), inflammatory bowel disease (10 -12), pulmonary hypertension (13,14), acute lung injury (15,16), asthma (17), and chronic obstructive pulmonary disease (18 -21).…”
Section: Serotonin (5-hydroxytryptamine; 5-ht)mentioning
confidence: 99%